Comparative Transcriptomic Immune Responses of Mullet (Mugil cephalus) Infected by Planktonic and Biofilm Lactococcus Garvieae - Su, Feng-Jie; Periyasamy, Thirunavukkarasu; Chen, Meei-Mei (Frontiers in Cellular and Infection Microbiology, 2022)
Lactococcus garvieae is an important pathogen of fish, associated with high rates of mortality and infection recurrence in summer or stressful conditions. Chronic infection and disease recurrence have also been reported to be associated with biofilms. However, the impact of biofilm and planktonic bacterial infection on fish immune responses remains unclear. In this study, de novo sequencing was used to compare differences of the spleen transcriptome in planktonic- and biofilm-infected mullets. Among the 181,024 unigenes obtained, 3,392 unigenes were associated with immune response genes. Comparative analysis of the gene expression between infection with the L. garvieae planktonic type and biofilm type identified a total of 3,120 and 3,489 differentially expressed genes in response to planktonic and biofilm infection, respectively, of which 1,366 and 1,458 genes were upregulated, and 1,754 and 1,458 genes were downregulated, respectively. Gene ontology enrichment analysis of immune genes identified genes involved in the complement system, toll-like receptor signaling, and antigen processing, which were further verified by qPCR. Additionally, genes encoding TLR2, IL-1β, TNF-α, C7, and MHC class II peptides were downregulated in response to biofilm infection. Importantly, the results show that biofilm infection induces a different immune pathway response compared with planktonic bacterial infection and, furthermore, illustrates that the prevention of biofilm formation may be a necessary and new strategy for controlling bacterial infection in aquaculture.